Diphyllobothrium stemmacephalum Cobbold, 1858 (Diphyllobothriidea) from common bottlenose dolphin, Tursiops truncatus (Montagu) from the Texas Gulf coast, USA - Sánchez, Sophia M.; Goldstein, Liat Y.; Dronen, Norman O. (Zootaxa, 2018)
Cobbold (1858) established Diphyllobothrium Cobbold, 1858 with the description of Diphyllobothrium stemmacephalum Cobbold, 1858 from the common harbor porpoise, Phocoena phocoena (Linnaeus) (Phocoenidae), from the North Sea off Scotland. Diphyllobothrium stemmacephalum typically has been reported from a number of Phocoenidae and Delphinidae hosts from a variety of localities: common harbor porpoise from the northern Atlantic Ocean, Baltic Sea and Black sea (e.g. Cobbold, 1858; Delyamure 1955; Delyamure 1968; Delyamure 1971; Delyamure et al. 1985; Anderson, 1987); bottlenose dolphin, Tursiops truncatus (Montagu), from the Gulf of Mexico (Ward & Collins 1959), the Black sea (Delyamure et al. 1985); common harbor porpoise off Newfoundland (Brattey & Stenson 1995), the Black Sea (Krivokhizin & Birkun 1994 [see Yera et al. 2008]), off Denmark (Herreras et al. 1997); long-finned pilot whale, Globicephala melas [Traill], North Atlantic off Faroe Island (Balbuena & Raga 1993); Atlantic white-sided dolphin, Lagenorhynchus acutus [Gray], off Massachusetts (Olson & Caira 1999).